Social networking associated with the dissemination of fake news in the pandemic of COVID-19 in Brazil. Integrative literature review (Research, Society and Development, 2022)
Objective: To identify the main media associated in the dissemination of fake news in times of pandemic of COVID-19 in Brazil. Methodology: This is an integrative literature review conducted by searching the databases of the Virtual Health Library (VHL), Scientific Electronic Library Online (SCIELO), National Library of Medicine (PUBMED) and Google Scholar, using as descriptors "COVID-19", "Social Media", "Public Health" and "Fake News". Inclusion criteria were: those that addressed the theme Social Media and Fake News; articles available in Portuguese, English, and published between the years 2020 and 2021. Results: Nine articles were identified that met the selected requirements, where it was evident that social networks are directly associated with fake news; moreover, one of the most cited was WhatsApp, followed by Facebook, Twitter, Instagram and YouTube. The social networks during the pandemic of COVID-19, were considered the major disseminators of fake news, attacking authorities, measures to confront the disease as social isolation, use of masks, and especially against immunizers, practiced even by the president of the Republic. The disinformation spread by social networks has directly impacted the health of the population and the health teams. Final considerations. There must be measures to combat and monitor the information shared by social networks, as well as penalties for individuals who use these tools with ill intent.